Evolution of Anomaly-Specific Techniques in Infant Ear Molding: A 10-Year Retrospective Study. Issue 2 (8th June 2022) - Charipova, Karina; Rogers, Ashley; Barra, Christina; Baker, Stephen B.
Abstract : Background: Congenital ear anomalies occur in at least one-third of the population, and less than one-third of cases self-correct. Ear molding is an alternative to surgery that spares operative morbidity and allows for significantly earlier intervention. In this retrospective study, the senior author (S.B.B.) developed a tailored approach to each specific type of ear deformity. The use of modifications to adapt standard ear molding techniques for each unique ear are described. Methods: The authors conducted a retrospective, institutional review board–approved study of 246 patients who underwent ear molding performed by a single surgeon. The procedure reports for each case were reviewed to develop stepwise customization protocols for existing EarWell and InfantEar systems. Results: This review included 385 ears in 246 patients. Patient age at presentation ranged from less than 1 week to 22 weeks. Presenting ear deformities were subclassified into mixed (37.4 percent), helical rim (28.5 percent), prominent (10.6 percent), lidding/lop (9.3 percent), Stahl ear (3.6 percent), conchal crus (3.3 percent), and cupping (2.8 percent). Two patients (0.8 percent) had cryptotia. Deformity subclass could not be obtained for 11 patients (4.5 percent). Recommended modifications to existing ear correction systems are deformity-specific: cotton-tip applicator/setting material (Stahl ear), custom dental compound mold (lidding/lop and cupping), scaphal wire (helical rim), cotton-tip applicator/protrusion excision (prominent), and custom dental compound stent (conchal crus). Conclusions: Presentation of ear anomalies is heterogenous. This 10-year experience demonstrates that the approach to ear molding should be dynamic and customized, using techniques beyond those listed in system manuals to complement each ear and to improve outcomes. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.